Effect of Underwater Insertion on Intracochlear Pressure - Riemann, Conrad; Sudhoff, Holger; Todt, Ingo (Frontiers in Surgery, 2020)
Background The importance of intracochlear pressure during cochlear electrode insertion for the preservation of residual hearing has been widely discussed. Various aspects of pre-insertional, intra-insertional, and post-insertional relevant conditions affect intracochlear pressure. The fluid situation at the round window during electrode insertion has been shown to be an influential factor. Aims/Objectives The aim of the study was to compare various insertion techniques in terms of the fluid situation at the round window. Material and Methods We performed insertion of cochlear implant electrodes in a curled artificial cochlear model. We placed and fixed the pressure sensor at the tip of the cochlea. In parallel to the insertions, we evaluated the maximum amplitude of intracochlear pressure under four different fluid conditions at the round window: 1) hyaluronic acid, 2) moisturized electrode, dry middle ear, 3) middle ear filled with fluid (underwater), and 4) moisturized electrode, wet middle ear, indirectly inserted. Results We observed the insertional intracochlear pressure is dependent on the fluid situation in front of the round window. While the lowest amplitude changes could be observed for the moisturized electrode in a wet middle ear indirectly inserted (0.13 mmHg ± 0.07), the highest values could be observed for insertion through hyaluronic acid in front of the round window (0.64 mmHg ± 0.31). Conclusions The fluid state in front of the round window influences the intracochlear pressure value during cochlear implant electrode insertion. An insertion of a moisturized electrode through a wet middle ear indirectly inserted generates experimentally the lowest pressure values.